Collecting biomedical and social data in a longitudinal survey: A comparison of two approaches. (1st October 2019) - Brown, Matt; Gilbert, Emily; Calderwood, Lisa; Taylor, Kate; Morgan, Hannah
Abstract : The inclusion of the collection of biomeasures within social surveys, and longitudinal surveys in particular, is becoming ever more common. Combining objective measurements of health with detailed information about lifestyles and behaviour collected over long periods of time offers enormous research potential.Studies that combine an interview with the collection of biomeasures can be conducted in various ways. One model is that field interviewers make initial contact with participants, conduct the interviews and arrange follow-up visits for a nurse to collect the biomeasures. Alternatively, field interviewers can be trained to collect biomeasures, but there remain questions about whether the quality of data collected is comparable to that collected by a nurse. Other studies invite participants to visit clinics, but this can be very costly in a large-scale national study. There is no consensus on the optimal strategy for combining a social survey with the collection of biomeasures.The 1970 British Cohort Study (BCS70) is a longitudinal birth cohort study which began in 1970. The 11th sweep of the study began in 2016, when study members were aged 46, and included an interview component alongside the collection of a range of biomeasures.The first phase of fieldwork was conducted using a new approach where nurses conducted all of the data collection. Midway through fieldwork BCS70 switched to a two-stage approach where interviews were conducted by interviewers followed by a separate nurse visit. This presented a unique opportunity to evaluate the success of the two approaches.